Peningkatan pengetahuan programmer prolanis terkait diabetes self-management selama puasa ramadan - Sugiharto Sugiharto; Sulastri Sulastri; Wiwiek Natalya (THE JOURNAL OF Nursing Management Issues, 2026)
Background: Ramadan fasting could provide numerous benefits for the body. However, it could also cause acute complications for people with diabetes. Therefore, consultation before fasting is crucial. Healthcare workers must have sufficient knowledge to provide accurate, evidence-based information. Purpose: To increase the knowledge of non-communicable disease (NCD) programmers and PROLANIS. Method: This community service program involved all non-communicable disease (NCD) and PROLANIS programmers. Education regarding diabetes and Ramadan was provided in accordance with International Diabetes Federation guidelines, as well as a fasting risk assessment using the "SHIYAM" application. Results: Twenty-four participants, including doctors, nurses, and midwives, took pre- and post-tests. The results showed a significant increase in knowledge (p <0.001). Conclusion: Structured education for NCD and PROLANIS programmers is very beneficial in preparing healthcare workers to provide health education to people with diabetes so they can fast safely and without complications. It is hoped that healthcare workers can apply their knowledge and conduct comprehensive assessments in primary healthcare facilities. Keywords: Self-Management; Knowledge; PROLANIS; Ramadan Fasting Risk Assessment; Type 2 Diabetes Mellitus. Pendahuluan: Puasa Ramadan dapat memberikan banyak manfaat bagi tubuh. Tetapi juga dapat menyebabkan komplikasi akut bagi diabetisi. Sehingga konsultasi sebelum berpuasa sangat penting. Tenaga kesehatan harus memiliki pengetahuan yang cukup untuk memberikan informasi yang tepat sesuai panduan dan berbasis bukti. Tujuan: Meningkatkan pengetahuan programmer penyakit tidak menular (PTM) dan PROLANIS. Metode: Pengabdian kepada masyarakat ini melibatkan seluruh programmer penyakit tidak menular dan PROLANIS. Edukasi yang diberikan mengenai diabetes dan ramadan sesuai panduan dari Internasional Diabetes Federation, juga pengkajian risiko berpuasa menggunakan aplikasi “SHIYAM”. Hasil: Sebanyak 24 peserta terdiri dari dokter, perawat, dan bidan telah mengikuti pretest dan posttest. Hasilnya menunjukkan peningkatan pengetahuan yang signifikan (p <0.001). Simpulan: Pendidikan terstruktur bagi programmer PTM dan PROLANIS sangat bermanfaat dalam menyiapkan tenaga kesehatan untuk memberikan pendidikan kesehatan bagi diabetisi agar dapat menjalankan puasa dengan aman dan bebas dari komplikasi. Diharapkan tenaga kesehatan dapat mengaplikasikan pengetahuannya dan melakukan pengkajian secara komprehensif di fasilitas kesehatan pratama. Kata kunci: Diabetes Melitus Tipe 2; Diabetes Self-Management; Knowledge; Pengkajian Risiko Puasa Ramadan; PROLANIS.